Utilization Of Coconut Dregs As An Alternative Medium For The Growth Of Bacillus Subtilis And Escherchia Coli - Dewita Nggua; Erni Yohani Mahtuti (Poltekkes Kemenkes Mataram, 2024)
Coconut dregs are waste produced after processing coconuts into coconut oil. Coconut pulp has a high nutritional content which can be used for bacterial growth. The nutritional content of coconut dregs is 38.1% carbohydrates, 5.6% crude protein, 16.3% crude fat, 31.6% crude fiber, 2.6% ash content and 5.5% water content. The research used coconut dregs as an alternative medium for the growth of gram-negative and gram-positive bacteria. In the trials, B. subtilis and E. coli bacteria were used. The type of research used was a true experiment with a completely randomized design. The results of the research showed that the highest average number of colonies on the coconut dregs alternative media was in treatment A1, namely the average of B.subtilis colonies was 50.6 x 10² CFU/mL and E.coli 36 .6 x 10² CFU/mL while the control media averaged B.subtilis colonies 75 x 10² CFU/mL and E.coli 86.3 x 10² CFU/mL. The results of statistical tests using anova p<0.05 with a sig value of 0.001 show that there is an influence of differences in the concentration of coconut dregs and agar as an alternative medium for bacterial growth. The post hoc test compares the concentration between treatment A1 and control with a sig p value of >0.05 (0.250), namely There is no significant difference, while the concentration between treatments A2, A3 and A4 with control has a sig p value <0.05, namely 0.000, meaning there is a significant difference. So treatment A1 is the best treatment for the growth of B.subtilis and E.coli bacteria.